Performance Study of Multi-Path in VANETs and Their Impact on Routing Protocols - Wu, Jing; Wang, Yuhao (Scientific Research Publishing, 2011)
Modeling complicated vehicular traffic behavior and analyzing effects on the communication performance of routing protocols taken by environmental factors have been a challenging task for the past several years. In this paper, we study the performance of multi-path routing protocol. Then, we investigate both multi-path and single-path routing protocol and analyze characteristics such as network connectivity, vehicle-node density etc. To better understand this phenomenon, we use mobility model with different parameters and evaluate the performance of routing protocols (Ad-hoc On-Demand Distance Vector and Ad-hoc On-demand Multipath Distance Vector routing protocols) through NS2 platform. The simulation results show the significance of multi-path on the throughput, loss and average delay of VANETs. The results of this paper may be used to study designing route protocols and applications of VANET.
Keywords: Vehicular Ad Hoc Networks(VANETs); Multi-Path; AODV; AOMDV